Hammersmith Infant Neurological Examination in low‐risk infants born very preterm: a longitudinal prospective study. (17th March 2022) - Romeo, Domenico M.; Apicella, Massimo; Velli, Chiara; Brogna, Claudia; Ricci, Daniela; Pede, Elisa; Sini, Francesca; Coratti, Giorgia; Gallini, Francesca; Cota, Francesco; Bovis, Francesca; Vento, Giovanni; et al.
Abstract: Aim: To describe the profile of global and single items of the Hammersmith Infant Neurological Examination (HINE) in a population of low‐risk infants born very preterm during the first year of life. Method: The HINE was performed at 3, 6, 9, and 12 months' corrected age in a population of low‐risk infants born preterm with a gestational age of fewer than 32 weeks and with normal or minimal changes on neuroimaging. Results: A total of 174 infants born preterm (96 males, 78 females; mean gestational age = 27 weeks [SD = 1.8], range 23–31 weeks) fulfilled the inclusion criteria. The 10th centile cut‐off score with median and range was reported for the HINE global and subsection scores. A progressive increase in global HINE scores was observed. Most of the single items, especially those related to tone, posture, and reflexes, showed progressive maturation. Interpretation: Our results, which provide longitudinal data for single‐item and global scores in a population of low‐risk infants born very preterm, can be used as a reference in both clinical and research settings to monitor early neurological signs in these infants. These data could be used as normative data when examining low‐risk infants born preterm. Abstract : This original article is commented on by Cao and Huang on pages 813‐814 of this issue.